PROBLEMATIKA PERKAWINAN DINI PADA MASYARAKAT ADAT SUKU ANAK DALAM BATIN SEMBILAN STUDI KASUS DI DESA NYOGAN, KECAMATAN MESTONG, KABUPATEN MUARO JAMBI (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of customary law within the Suku Anak Dalam (SAD) Batin 9 community in addressing the practice of early marriage and to examine the extent to which these customary values align with the principles of Maqasid al-Shariah. The research employs a qualitative approach with a descriptive-analytical method. Data were collected through interviews with traditional leaders, village authorities, and individuals involved in early marriages, as well as direct observation of customary ceremonies and family deliberation processes. The findings reveal that within the Batin 9 customary legal system, decisions regarding early marriage are reached through extended family deliberation and an assessment of the couple’s preparedness by customary elders. Customary norms emphasize physical, psychological, and economic readiness as the basis for validating a marriage, rather than solely relying on biological age. This principle reflects the values of ḥifẓ al-nafs (protection of life) and ḥifẓ al-nasl (protection of lineage) as articulated in the Maqasid al-Shariah. However, the practice of conducting marriages without official state registration creates legal and social complications, particularly concerning inheritance rights and access to public services. The study concludes that the SAD Batin 9 customary law embodies protective values that are consistent with the objectives of Islamic law, yet greater harmonization with Indonesian positive law is necessary to ensure comprehensive child protection. Integrating customary norms, religious principles, and national law is essential to achieving public welfare (maṣlaḥa) for indigenous communities without diminishing their cultural identity.